2013
DOI: 10.1111/j.2047-2927.2012.00049.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide identification of Sox8‐, and Sox9‐dependent genes during early post‐natal testis development in the mouse

Abstract: Genome-wide identification of Sox8-, and Sox9-dependent genes during early post-natal testis development in the mouse F. Chalmel,*,a A. Lardenois,*,a I. Georg, †, ‡,k F. Barrionuevo, †,** P. Demougin, § B. J egou,*, ¶ G. Scherer † and M. Primig* *Inserm, U1085-Irset, University of Rennes 1, Rennes, France, †Institute of Human Genetics, University of Freiburg, Freiburg, Germany, ‡Faculty for Biology, University of Freiburg, Freiburg, Germany, §Biozentrum, University of Basel, Basel, Switzerland, ¶EHESP School o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 95 publications
1
12
0
Order By: Relevance
“…The results of this study are in agreement with a previous finding that SOX9 is present in both sexes, but in one of the first molecular events in the male pathway is upregulated in Sertoli cell precursors (which are essential for testis differentiation) by the primary sex-determining trigger interacting with an evolutionarily conserved sequence within SOX9 [29]. In mammals, the SOX8 and SOX9 transcription factors are involved, among other things, in sex differentiation, male gonad development and adult maintenance of spermatogenesis [30].…”
Section: Discussionsupporting
confidence: 82%
“…The results of this study are in agreement with a previous finding that SOX9 is present in both sexes, but in one of the first molecular events in the male pathway is upregulated in Sertoli cell precursors (which are essential for testis differentiation) by the primary sex-determining trigger interacting with an evolutionarily conserved sequence within SOX9 [29]. In mammals, the SOX8 and SOX9 transcription factors are involved, among other things, in sex differentiation, male gonad development and adult maintenance of spermatogenesis [30].…”
Section: Discussionsupporting
confidence: 82%
“…While Sox8 inactivation does not affect testis determination [47], analyses of Sox8/Sox9 double mutants showed that SOX8 is able to compensate for the loss of Sox9 after sex determination [9,30,48]. Moreover, SOX8 and SOX9 activate common target genes such as Amh and Cbln4 [32,48]. Therefore, we propose that SRY and its target gene SOX8 partially compensate for the absence of SOX9 in XY Ctnnb1/Sox9 DKO supporting cells and promote Sertoli cell differentiation (Fig.…”
Section: Gonad Identity Without Sox9 and Beta-cateninmentioning
confidence: 90%
“…In our XY Ctnnb1/Sox9 DKO model, in addition to Sry, Sox8 is the only Sox gene expressed during the initial events of masculinization. While Sox8 inactivation does not affect testis determination [47], analyses of Sox8/Sox9 double mutants showed that SOX8 is able to compensate for the loss of Sox9 after sex determination [9,30,48]. Moreover, SOX8 and SOX9 activate common target genes such as Amh and Cbln4 [32,48].…”
Section: Gonad Identity Without Sox9 and Beta-cateninmentioning
confidence: 94%
“…The direct transcriptional targets of Sox10 include genes encoding proteolipid protein, extracellular superoxide dismutase, and pleiotrophin in rat Schwannoma cells [10]. Moreover, genome-wide analysis has revealed hundreds of genes that are potential binding targets for Sox9 and/or Sox8 in mice and rats [11, 12]. Because of the functional redundancy of the different SoxE proteins in mammals [13], it may be difficult to determine their targets.…”
Section: Introductionmentioning
confidence: 99%